EXPLORING FACTORS OF INSECURITY OF CHRISTIAN MINORITY IN DISTRICT OKARA (Contemporary Journal of Social Science Review, 2024)
This study finds out the fear of isolation and insecurity of minorities regarding religious extremism and state institutions. This study aims to analyze the isolation and other insecurities of minorities, like identity insecurity, life insecurity, and job insecurity. In order to carry out this research, quantitative methodology simple random method was applied. Data was collected through a self-administered questionnaire by drawing a sample of 400 Christian through a simple random sampling technique. The study explored three factors of insecurity among Christians i.e., structural inequality, intolerance and support and community discrimination. The study suggests the mutual respect and acceptance of difference across religions to reduce the insecurity among the religious minorities.